Influence of Environmental Factors on the Physico-Chemical and Bacteriological Quality of Well and Borehole Water in Rural Communities of Udenu Lga of Enugu State, Nigeria - Chukwuma, Obeta Michael; Ifeanyichukwu, Mamah Kingsley (Pakistan Journal of Nutrition, 2018)
Background and Objective: The influence of environmental factors on well and borehole water quality in rural communities in Nigeria was investigated in this study. The objectives were to characterize/contrast the pollutants, determine the influence of environmental factors on the water quality and highlight the health implications of the findings. Methodology: Water samples were collected from ten boreholes and ten hand-dug wells in ten rural communities. Fifteen physico-chemical and bacteriological water quality parameters including: pH, Temperature, Electrical conductivity, Turbidity, Nitrate, Iron, Total dissolved solids, Sulphate, Alkalinity, Total hardness, Chloride, Calcium, Magnesium, Total coliform count and E. coli were analyzed. Results: The results of the analysis were reported based on the WHO standard. The analysis showed borehole samples exhibit higher concentration of natural pollutants while well samples exhibit higher concentration of anthropogenic pollutants. Principal Component Analysis (PCA) reduced the fourteen environmental variables influencing the water quality to five underlining components which explained 84.5% of the data matrix leaving 15.5% to other variables not used in the study. The extracted components included extent of source water protection, mineral properties of rocks and influence of vegetal cover. Conclusion: It is concluded that to avoid contamination, regulatory authorities should closely monitor well/borehole development in the area.